A review on the characterisation of natural fibres and their composites after alkali treatment and water absorption. (16th March 2017) - Chandrasekar, M.; Ishak, M. R.; Sapuan, S. M.; Leman, Z.; Jawaid, M.
ABSTRACT: Natural fibre-reinforced polymer matrix composites are gaining increased attention among the researchers due to their low density, biodegradability, abundance, good mechanical properties, etc. Significant amount of research works can be found on the material characterisation of natural fibres like hemp, flax, sisal, kenaf, coir and jute and their composites based on the polymer matrices. Natural fibres are hydrophilic in nature and exhibit poor interfacial adhesion between fibre and matrix. Modification of the fibre surface by chemical methods, such as alkalisation, benzoylation and acetylation, has been used by researchers to improve the above-mentioned shortcomings. This review paper focuses on the effect of alkali treatment on the material properties of various natural fibres and their composites along with their water absorption behaviour.